1969
DOI: 10.1111/j.1469-8986.1969.tb02869.x
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Repetition Rate Factors Which Influence the Auditory Evoked Potential in Man

Abstract: The slow component of the auditory evoked potential in man was investigated under various conditions which produced an increase in stimulus repetition rate. The left ear received a 1000 Hz tone once each 5 sec. Intervening stimuli, also of 1000 Hz, were presented to (1) the right ear, (2) both ears, and (3) the left ear. Their relative influence on response amplitude to periodic left ear stimulation was evaluated. The results indicated that: (1) intervening right ear stimulation reduced significantly response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 3 publications
1
10
0
Order By: Relevance
“…Further, N1 and P2 of the differential waveform were significant predictor variables of early and late peak amplitudes of the MMN. These results suggest that refractory effects may overlay/modify the morphology of the MMN waveform consistent with previous findings (Butler 1968(Butler , 1972Butler et al 1969;Picton et al 1972;Näätänen et al 1988;May et al 1999). As stated earlier, in the standard oddball approach, the standards are presented more frequently and with shorter ISIs in the stimulus trains than the deviants.…”
Section: Mmn and Differential Waveform 10supporting
confidence: 91%
See 1 more Smart Citation
“…Further, N1 and P2 of the differential waveform were significant predictor variables of early and late peak amplitudes of the MMN. These results suggest that refractory effects may overlay/modify the morphology of the MMN waveform consistent with previous findings (Butler 1968(Butler , 1972Butler et al 1969;Picton et al 1972;Näätänen et al 1988;May et al 1999). As stated earlier, in the standard oddball approach, the standards are presented more frequently and with shorter ISIs in the stimulus trains than the deviants.…”
Section: Mmn and Differential Waveform 10supporting
confidence: 91%
“…Others, however, have reported to the contrary. For example, Butler (1968Butler ( , 1972 and Butler et al (1969) demonstrated that when stimuli were interleaved between trains of test stimuli, the N1-P2 amplitude to the test stimuli decreased relative to when the test stimuli were presented alone. That is, increasing the separation in frequency between the test stimuli and the interleaved stimuli resulted in a smaller decrease in the N1 amplitude.…”
Section: Mmn and Differential Waveform 3 An Evaluation Of The Mismatcmentioning
confidence: 99%
“…There is no entirely compelling evidence, however, for this belief for MMN to pitch changes~Frequency-MMN!. On the contrary, the auditory system reveals a tonotopic organization from cochlea throughout cortex Pantev et al, 1988;Romani, Williamson, & Kaufman, 1982!. Stimulus repetition leads to repeated initiation of patterns of neural activity that habituates as a function of repetition rate~e.g., Butler, Spreng, & Keidel, 1969;Näätänen et al, 1988;Picton, Woods, & Proulx, 1978!. In the classic oddball protocol, the neural response to standard stimuli is suppressed by these refractory effects.…”
mentioning
confidence: 97%
“…Basically, it is known that the amplitude of evoked potentials depends at all levels of the auditory pathway on the stimulation rate -the amplitude decreases with increasing stimulation rate; this effect is amplified towards the auditory cortex [52,53].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%